ANATOMI KONFLIK ANTARA PENGEMUDI OJEK ONLINE DENGAN OJEK KONVENSIONAL DI KOTA SURAKARTA - Nurul Hasanah; Triyanto; Rusnaini (Asosiasi PPKn, 2019)
The purpose of this research is to know the: (1) what are the factors that encourage the occurrence of conflict between the drivers of online motorcycle taxi with conventional motorcycle taxi in the city of Surakarta; (2) the efforts of the government of the city of Surakarta in resolving the conflict between the drivers of online motorcycle taxi with conventional motorcycle taxi in the city of Surakarta; and (3) the impact of the existence of a conflict between the drivers of online motorcycle taxi with conventional motorcycle taxi in the city of Surakarta. The research method used descriptive research method with a qualitative research approach. Research subject retrieval technique using a purposive sampling and snowball sampling. The technique of data collection by observation, interviews and study of documents. Test the validity of the data using triangulation of data and methods. Data analysis techniques using interactive data analysis that has stages, namely: (1) data collection; (2) the reduction of data; (3) the presentation of data and (4) the verification or conclusion. Based on the results of the research, it can be concluded that: (1) factors that encourage the occurrence of conflict between the drivers of online motorcycle taxi with conventional motorcycle taxi in the city of Surakarta namely the absence of regulation which regulates clearly about the existence of online-based transport as well as the existence of economic interests in the form of competition in getting passengers and fulfillment needs is hampered.; (2) the efforts made the Government city of Surakarta in resolving the conflict between the drivers of online motorcycle taxi with conventional motorcycle taxi in the city of Surakarta, namely by doing mediation. In the mediation efforts achieved a mutual agreement that is the existence of a red-zone assignment in some places contained conventional taxi bases, such as in the Solo Balapan Station, Purwosari Station and Tirtonadi Terminal. At this point in the red zone, online motorcycle taxi drivers prohibited doing pick up passengers up to a predetermined distance.; and (3) the impact caused by the conflict between the drivers of online motorcycle taxi with conventional motorcycle taxi in the city of Surakarta, namely increasing solidarity in-group on the online motorcycle taxi drivers, there arose the inherent shakiness and cracks in the unity of the group of conventional motorcycle taxi drivers, the fall of human sacrifice on online motorcycle taxi drivers, the dominance of online motorcycle taxi drivers resulted in adherence to conventional motorcycle taxi drivers, as well as the existence of a sense of fear in the community and surrounding areas of Surakarta.   Full Paper